Estudio de prefactibilidad para la instalación de una planta productora de aceite vegetal a base de semillas de uva (Vitis vinifera) - Bambaren Vega, Ivanna Nataly (2021)
The project’s main objective is to determine the economic, technological and market installation viability of an oil production plant of grape seeds for human consumption. This oil contains a high amount of vitamin E and antioxidants, so it will focus on the people who are looking forward to consume healthy products. It has been proven that there is enough technology to make the project, as well as there is people interested in its consumption and the positive environmental impact on reusing a sub product of the grape. The distribution will be made through supermarkets and healthy stores. Regarding the demand of the product, it has been increasing in the past years showing the population’s interest. A demand of 100, 375 containers of 250 ml was determined for 2021. For the setting of the plant localization, it was determined to be on the province of Ica, which is one of the three biggest producers of grape in the country; and with the purpose of selecting a more delimited place, factors were analyzed such as the price of the field and the price of the transportation of the final product, ended in choosing Chincha. In regards to the size of the plant, it contains 122,417 containers or 28,095 kg of oil, being able to cover until the last year of the project. The Guerchet method was used to determine the totality of the meters of the plant and it turned to be of 489 square meters, taking into consideration additional areas required. About the economic-financial assessment, it will have an initial investment of S/.464,060, which 30% will be financed by a bank and the other 70% with equity capital. Consequently, project is profitable thanks to the following indicators: VANE = 239, 809 and VANF = 259,126; also the values of the TIRE = 26.83% and TIRF = 30,94% are greater than opportunity cost: COK = 14.22% and weighted average cost of capital: WACC = 12.63%.